Normative data for regional sweat sodium concentration and whole-body sweating rate in athletes - Baker, L. B.; Barnes, K. A.; Anderson, M. L.; Passe, D. H.; Stofan, J. R. (Journal of Sports Sciences, 2016)
The purpose of this study was to establish normative data for regional sweat sodium concentration ([Na+]) and whole-body sweating rate in athletes. Data from 506 athletes (367 adults, 139 youth; 404 male, 102 female) were compiled from observational athlete testing for a retrospective analysis. The participants were skill/team-sport (including American football, baseball, basketball, soccer and tennis) and endurance (including cycling, running and triathlon) athletes exercising in cool to hot environmental conditions (15-50°C) during training or competition in the laboratory or field. A standardised regional absorbent patch technique was used to determine sweat [Na+] on the dorsal mid-forearm. Whole-body sweat [Na+] was predicted using a published regression equation (y = 0.57x+11.05). Whole-body sweating rate was calculated from pre- to post-exercise change in body mass, corrected for fluid/food intake (ad libitum) and urine output. Data are expressed as mean ± SD (range). Forearm sweat [Na+] and predicted whole-body sweat [Na+] were 43.6 ± 18.2 (12.6-104.8) mmol/L and 35.9 ± 10.4 (18.2-70.8) mmol/L, respectively. Absolute and relative whole-body sweating rates were 1.21 ± 0.68 (0.26-5.73) L/h and 15.3 ± 6.8 (3.3-69.7) ml/kg·h, respectively. This retrospective analysis provides normative data for athletes` forearm and predicted whole-body sweat [Na+] as well as absolute and relative whole-body sweating rate across a range of sports and environmental conditions.